1963
DOI: 10.1530/jrf.0.0050433
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Degeneration in the Ram and Its Relation to the Temperature of the Scrotum

Abstract: Summary. The semen collected from twelve Merino rams was ex¬ amined before and after they were exposed during 3 days to two 6-hr periods in a climate room at 40-5°C , After recovery from the first experiment, the same rams were divided into three groups of four. Two groups were exposed to the same heat treatments as before and the third group stood in the climate room for 12 hr at 21°C and 6-8 mm Hg vapour pressure. Water at 17 to 19°C was circulated around the scrotum of one group of rams exposed to heat an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
4

Year Published

1970
1970
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 12 publications
3
25
0
4
Order By: Relevance
“…The reduction in semen characteristics such as mass activity, percentage progressive sperm motility, live/dead cell ratio and sperm cell concentration (Spermatozoa/ml) in all the bucks during scrotal insulation was in agreement with previous findings (Austin et al, 1961, Moule and Waites, 1963, Ajala et al, 2001) that elevated testicular temperature will affect normal sperm characteristics. Mieusset and Bujan, (1995) reported that increased testicular heat usually drives towards rapid shutdown of cellular activities which is often the cause of testicular degeneration and this agrees with results of this study since testicular temperature which 0 reached 43.5 C caused testicular degeneration responsible for changes in semen physical characteristics such as color and viscosity.…”
Section: Discussionsupporting
confidence: 92%
“…The reduction in semen characteristics such as mass activity, percentage progressive sperm motility, live/dead cell ratio and sperm cell concentration (Spermatozoa/ml) in all the bucks during scrotal insulation was in agreement with previous findings (Austin et al, 1961, Moule and Waites, 1963, Ajala et al, 2001) that elevated testicular temperature will affect normal sperm characteristics. Mieusset and Bujan, (1995) reported that increased testicular heat usually drives towards rapid shutdown of cellular activities which is often the cause of testicular degeneration and this agrees with results of this study since testicular temperature which 0 reached 43.5 C caused testicular degeneration responsible for changes in semen physical characteristics such as color and viscosity.…”
Section: Discussionsupporting
confidence: 92%
“…A decrease in the proportion of unstained spermatozoa with an increase in air temperature and humidity is expected in view of several reports including those of Waites & Setchell (1964), and Moule & Waites (1963 …”
mentioning
confidence: 82%
“…Esse aumento de temperatura leva a sérias conseqüên-cias para a qualidade do sêmen e subseqüentemente para a fecundação e a sobrevivência embrionária, interferindo diretamente sobre os resultados de fertilidade ao parto (Moule & Waites, 1963;Smith, 1971;Mucciolo et al, 1974;Cózer et al, 1979;Kishore & Rao, 1983;Mieusset et al, 1992).…”
Section: Introductionunclassified